Water use efficiency, biomass production, nitrogen and potassium uptake and yield of tomato (Lycopersicon esculentum cv. Ratan) Planta grown under surface drip and flood irrigation (Journal of the Asiatic Society of Bangladesh, Science, 2013)
An experiment was conducted in wooden boxes to evaluate water use efficiency, biomass production, nitrogen and potassium uptake and yield of tomato plants (Lycopersicon esculentum) grown under flood irrigation (FI) and surface drip irrigation (SDI). Leaf area, leaf area index, biomass production and yield of tomato plants were significantly (P